RESPON TANAMAN NILAM (Pogostemon cablin Benth) TERHADAP CEKAMAN KEKERINGAN - , SETIAWAN, Prof. Dr. Ir. Tohari, MSc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Patchouli (Pogostemon cablin Benth) is one of species which produce essential oil. It is known as Patchouli oil. In Indonesia, Patchouli oil is one of important economically. It occupies an area 24.718 ha which cultivate by 65.000 farmers in Indonesia. Yield losses from Patchouli were reported caused by global climate change (global warming). Global warming increases the effect both of frequency and intensity of El Nino which cause reduce rainfall. Low frequency and intensity rainfall, and increasing of global temperature cause the drought. Patchouli is known susceptible to drought stress. Now, there are three cultivars which produce high essential oil (290-375 kg/ha) with patchouli alcohol content about 32 â 33 %. They are Tapaktuan, Sidikalang, dan Lokseumawe. The aim of this research was evaluated resistance to drought stress degree on Patchouli cultivars. The field experiment was carried out from Nopember 2011 to Juli 2012 at the green house Research Institute for Spice and Medicine Crop, Bogor. The experimental design was laid-out in Randomized Completely Block Design with three replications as block. The experiment was involved two factors. Factor one was cultivars (Sidikalang, Lokseumawe, Tapaktuan dan Klon Bio-4). Factor two was watering- interval (once each 1, 3 , 6 and 9 days). All data were statistically analyzed using the analysis of variance procedure in SAS program to assess the differences of cultivars. Duncanâs Multiple Range Test would be tested to determine the significant differences among treatments. The details of data recorded were soil moisture, leaf water potential, relative water content, stomata conductivity, transpiration rate, photosynthetic rate, prolin content, plant height, sum of leaves, leaf area, specific leaf area, leaf area ratio, total length of root, root area, weight of root, weight of shoot, root/shoot ratio, crop growth rate and net assimilate rate, essential oil content per plant and patchouli alcohol content, and sensitivity index. The result showed that watering- interval once each nine days significantly decreased of soil moisture, relative water content, leaf water potential, stomata conductivity, transpiration rate, photosynthetic rate, prolin content, plant height, sum of leaves, leaf area, specific leaf area, and essential oil content per plant, and increased root area and prolin content. Sidikalang and Lokseumawe showed more tolerant to drought stress than Tapaktuan. The highest essential oil content per plant showed that Loksemawe, followed by Tapaktuan and Sidikalang. Bio-4 showed that the lowest essential oil per plant.